1993
DOI: 10.1016/0301-4622(93)85003-z
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of Raman vibrational bandwidths in poly(rA) and rAMP

Abstract: Isotropic and anisotropic spontaneous Raman spectra were obtained from solutions of polyjrA) and rAh4P in buffer. The temperature dependence of these spectra was measured to elucidate the influence of macromolecular dynamics and solvent dynamics on the bandwidths of base vibrations in the single stranded polynucleotide poly(rA). The temperature dependence of a bandwidth depends upon the particular vibration under study. The bands can for the larger part be described by Lorentz functions. When fitted by Voigt f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Isotropic and anisotropic spontaneous Raman spectra were obtained from solutions of poly(rA) and rAMP in buffer [6]. The temperature dependence of these spectra was measured to elucidate the influence of macromolecular dynamics and solvent dynamics on the bandwidths of base vibrations in the single stranded polynucleotide poly(rA) [6].…”
Section: Introductionmentioning
confidence: 99%
“…Isotropic and anisotropic spontaneous Raman spectra were obtained from solutions of poly(rA) and rAMP in buffer [6]. The temperature dependence of these spectra was measured to elucidate the influence of macromolecular dynamics and solvent dynamics on the bandwidths of base vibrations in the single stranded polynucleotide poly(rA) [6].…”
Section: Introductionmentioning
confidence: 99%
“…A study into the vibrational bandwidths of adenine in the polynucleotide poly(rA) has been done [8]. The bandwidths obtained for poly(rA) were compared with those of the mononucleotide rAMP, in the temperature range where poly(rA) gradually changes from a base stacked structure to an unstacked structure [8].…”
Section: Introductionmentioning
confidence: 99%
“…The bandwidths obtained for poly(rA) were compared with those of the mononucleotide rAMP, in the temperature range where poly(rA) gradually changes from a base stacked structure to an unstacked structure [8]. The influence of macromolecular dynamics and solvent dynamics on the bandwidths of base vibrations in the single stranded polynucleotide poly(rA) have been elucidated [8].…”
Section: Introductionmentioning
confidence: 99%
“…Isotropic and anisotropic spontaneous Raman spectra were obtained from solutions of poly(rA) and rAMP in buffer [9]. The temperature dependence of these spectra was measured to elucidate the influence of macromolecular dynamics and solvent dynamics on the bandwidths of base vibrations in the single stranded polynucleotide poly(rA) [9]. It has been found that the full widths at half-maximum (FWHM) of the bands in poly(rA) are typically [9] of the order of 12-20 cm −1 .…”
Section: Introductionmentioning
confidence: 99%